Isotopic and Geochemical Assessment of in Situ Biodegradation of Chlorinated Hydrocarbons - Kirtland, Brian C.; Aelion, C. Marjorie; Stone, Peter A.; Hunkeler, Daniel (My University, 2003)
Currently there is no in situ method to detect and quantify complete mineralization of chlorinated hydrocarbons (CHCs) to CO2. Combined isotopic measurements in conjunction with traditional chemical techniques were used to assess in situ biodegradation of trichloroethylene (TCE) and carbon tetrachloride (CT). Vadose zone CHC, ethene, ethane, methane, O2, and CO2 concentrations were analyzed using gas chromatography over 114 days at the Savannah River Site. δ13C of CHC and δ13C and 14C of vadose zone CO2, sediment organic matter, and groundwater dissolved inorganic carbon (DIC) were measured. Intermediate metabolites of TCE and CT accounted for ≤10% of total CHCs. δ13C of cis-1,2-dichloroethylene (DCE) was always heavier than TCE indicating substantial DCE biodegradation. 14C-CO2 values ranged from 84 to 128 percent modern carbon (pMC), suggesting that plant root-respired CO2 was dominant. 14C-CO2 values decreased over time (up to 12 pMC), and contaminated groundwater 14C-DIC (76 pMC) was substantially depleted relative to the control (121 pMC). 14C provided a direct measure of complete CHC mineralization in vadose zone and groundwater in situ and may improve remediation strategies.